Tooth extraction before radiotherapy is a risk factor for developing osteoradionecrosis of the jaws: A systematic review. (7th July 2020) - Lajolo, Carlo; Gioco, Gioele; Rupe, Cosimo; Troiano, Giuseppe; Cordaro, Massimo; Lucchese, Alberta; Paludetti, Gaetano; Giuliani, Michele
Abstract: Objectives: The aim of this systematic review was to estimate the osteoradionecrosis rate in patients with head and neck cancer due to teeth extraction performed before radiotherapy and to identify possible risk factors. Material and Methods: PRISMA protocol was used to evaluate and present the results. PubMed, Scopus and Web of Science were used as search engines: English full‐length papers of clinical studies, in peer‐reviewed journals, were investigated. Cumulative meta‐analysis was performed with a random effects model (PROSPERO registration code: CRD42018079986). Results: Among 2, 020 records screened, 8 were included in this review. Sixteen of 494 patients who underwent tooth extraction before radiotherapy developed osteoradionecrosis, with an osteoradionecrosis incidence of 2.2% (95% Confidence of Interval = 0.6–3.9, p  < .185, I 2  = 3, 044%). All cases were reported in the mandible. No other clinical risk factor for osteoradionecrosis was detected. Conclusions: Even if it is generally recommended to remove oral foci before radiotherapy, this systematic review confirmed that teeth extractions before radiotherapy represent a risk factor for osteoradionecrosis; the considerable amount of missing data prevented us from identifying other possible risk factors for osteoradionecrosis onset. Major efforts should be done to perform sounder methodological clinical investigations.